The role of long non-coding RNAs in the development of adipose cells - Albert Sufianov; Aferin Beilerli; Valentin Kudriashov; Tatiana Ilyasova; Yanchao Liang; Albert Mukhamedzyanov; Marina Bessonova; Andrey Mashkin; Ozal Beylerli (Non-coding RNA Research, 2023)
In recent times, the rising prevalence of obesity and its associated comorbidities have had a severe impact on human health and social progress. Therefore, scientists are delving deeper into the pathogenesis of obesity, exploring the role of non-coding RNAs. Long non-coding RNAs (lncRNAs), once regarded as mere ''noise'' during genome transcription, have now been confirmed through numerous studies to regulate gene expression and contribute to the occurrence and progression of several human diseases. LncRNAs can interact with protein, DNA, and RNA, respectively, and participate in regulating gene expression by modulating the levels of visible modification, transcription, post-transcription, and biological environment. Increasingly, researchers have established the involvement of lncRNAs in regulating adipogenesis, development, and energy metabolism of adipose tissue (white and brown fat). In this article, we present a literature review of the role of lncRNAs in the development of adipose cells.